Replication of Feline Syncytial Virus in Feline T-Lymphoblastoid Cells and Induction of Apoptosis in the Cells - Ikeda, Yasuhiro; Itagaki, Shin-lchi; Tsutsui, Shigeki; Inoshima, Yasuo; Fukasawa, Masashi; Tomonaga, Keizo; Tohya, Yukinobu; Maeda, Ken; Mochizuki, Masami; Miyazawa, Takayuki; Mikami, Takeshi (MICROBIOLOGY and IMMUNOLOGY, 1997)
Feline syncytial virus (FSV) was isolated from feline peripheral blood mononuclear cells of FSV-seropositive cats. When the susceptibility of feline T-lymphocytes to FSV was examined using three strains of FSV, FSV antigens were detected in the FSV-infected T-lymphoblastoid cells. Further, a diversity of biological properties, including replication kinetics and syncytia formation, was noted among the strains, and condensation of chromatin and the fragmentation of cellular DNA were observed in the infected cells. From these data, we conclude that FSV is lymphotropic and can induce apoptosis in the lymphocytes.